Onshoring Through Automation; Perpetuating Inequality? - Studley, Matthew (Frontiers in Robotics and AI, 2021)
Many analyses of the ethical, legal and societal impacts of robotics are focussed on Europe and the United States. In this article I discuss the impacts of robotics on developing nations in a connected world, and make the case that international equity demands that we extend the scope of our discussions around these impacts. Offshoring has been instrumental in the economic development of a series of nations. As technology advances and wage share increases, less labour is required to achieve the same task, and more job functions move to new areas with lower labour costs. This cascade results in a ladder of economic betterment that is footed in a succession of countries, and has improved standards of living and human flourishing. The recent international crisis precipitated by COVID-19 has underlined the vulnerability of many industries to disruptions in global supply chains. As a response to this, “onshoring” of functions which had been moved to other nations decreases risk, but would increase labour costs if it were not for automation. Robotics, by facilitating onshoring, risks pulling up the ladder, and suppressing the drivers for economic development. The roots of the economic disparities that motivate these international shifts lie in many cases in colonialism and its effects on colonised societies. As we discuss the colonial legacy, and being mindful of the justifications and rationale for distributive justice, we should consider how robotics impacts international development.